The Relationships between Body Weight and Size of the Elongated Tortoise Shell, Indotestodo elongata at Khon Kaen Province, Thailand - ศรีประทีป กัลยา (KKU Science Journal, 2015)
The objective of this study is to find out the relationships between body weight and size of Indotestudo elongata shell by measuring on both carapace and plastron of animals. The study area is "Tortoise Village" or Ban Kok in Suan Mon Subdistrict, Mancha Khiri District. The sample size comprised of 160 juveniles (hatchling - 6 years), 54 adult males and 50 adult females. From regression coefficient analysis, the coefficient of determination (R2) of juveniles was 0.9642 - 0.9779, adult males and adult females were 0.9159 - 0.9468 and 0.9273 - 0.9458, respectively. The relationships between weight and length and weight and width of juveniles were higher than that of adults. The relative equation was Log W = 2.794log PL – log 3.181 (R2 = 0.9779, n = 160, p < 0.01). Moreover, the adult males had the highest relationship between weight and carapace width (CW) and the relative equation was Log W = 3.128log CW – log 3.535 (R2 = 0.9468, n = 54, p < 0.01). In addition, adult females had the highest relationship between weight and plastron length (PL) and the relative equation was Log W = 3.028log PL – log 3.705 (R2 = 0.9458, n = 50, p < 0.01). It had been found that this method could be used to estimate the weights of the tortoises using these equations with 99% confidence interval (p < 0.01). Therefore, regression coefficient analysis could be used to estimate weights and length and weight and width of elongated tortoise.